PETROLOGICAL AND GEOCHEMICAL STUDY OF HYDRO-VOLCANIC ROCKS OF ULAKAN FORMATION IN SOUTHEAST BALI - Mutmainnah, Puput
The study area is located in Klungkung Regency and Karangasem Regency, Bali Province. Bali is included in the Sunda Volcanic Arc where volcanic igneous rocks in the form of basalt lavas and their associations are found as products of volcanoes in the Tertiary Period (Ulakan Formation). Petrological analysis of volcanic rocks along with their geochemical composition can reflect the characteristics of the forming magma so that the tectonic setting and volcanic activity can be reconstructed. Data from outcrop observations and rock sampling used in this study are in the form of primary data which includes 24 volcanic rock samples (including as fragments of breccia) were analysed for petrography with 8 of them were analysed for rock geochemistry using X-Ray Fluorescence (XRF), Inductively Coupled Plasma - Optical Emission Spectrometry (ICP-OES), and Inductively Coupled Plasma Mass Spectrometry (ICP-MS). In addition, a total of 5 breccia matrix samples were analysed for petrography with 4 of them were analysed for microfossil content. Meanwhile, secondary data used in the research in the form of 13 samples of rock geochemical data came from previous published research and 8 samples came from previous final assignments. Volcanic eruptions that occurred in the Tertiary Period occurred effusively with a little explosive producing products in the form of basalt lava with its rock associations and tuff. Basalt lava with their associations are formed due to strong interactions between lava and water with the presence of basic sediments. There are four types of basalt lava structures that can be observed, namely massive lava, pillow lava, isolated pillow breccia, and broken pillow fragment breccia. The composition of basalt lava (including as breccia fragments) consists of phenocrysts of olivine, pyroxene, and a little plagioclase embedded in a fine crystal base of plagioclase, clinopyroxene, volcanic glass, and opaque minerals with intersertal texture. Based on the results of the geochemical analysis of the basalt lava, the volcanic magma has two types of saturation, namely highly silica unsaturated and silica saturated. The affinity of the magma formed is tholeiite to calc-alkaline, but has a high K content. The results of the Harker Diagram show that the volcanic magma has two different cogenetic trends. In addition, the differentiation of volcanic magma is closely related to the crystal fractionation process of olivine, pyroxene and plagioclase. The spider diagram analysis shows that the volcano was formed in a tectonic setting in the form of island arc subduction with indications of contamination of continental crust fragments that cause high K content in rocks.